Social policy and labour mobility in Europe - the gap between law and enforcement - Cremers, Jan (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
In this contribution, the author reflects on the gap between EU social policy Regulations and Directives related to cross-border labour mobility and the problems that legal and social practitioners encounter in the application of this regulatory frame. He assesses some basic fields of social policy and workers’ rights applicable in the area of labour mobility (free movement, posting of workers, coordination of social security) to demonstrate the disparity between the 'spirit of the law’ and the practical application of the legislation. This gap is often stemming from contradictions that are the result of the subordination of social rights to the economic freedoms.